A Case Control Study on Selected Maternal Risk Factors of Molar Pregnancy (Journal of Preventive and Social Medicine, 2021)
Background: The incidence of gestational trophoblastic disease varies dramatically in different regions of the world. While there are some geographical and racial variations, perhaps a higher incidence in Africa and Asia. The high incidence of molar pregnancy in some populations have been attributed to nutritional and socioeconomic factors. Some maternal biological factors also associated with molar pregnancy. This study aims to explore the various maternal risk factors associated with molar pregnancy.Methods: This case control study was carried out among 50 molar and 100 non-molar pregnant mothers admitted at in patient department of obstetrics and gynecology, Rajshahi Medical College Hospital from January to December 2011. The patients of molar pregnancies were selected on the basis of clinically diagnosed confirmed by ultrasonogram and histopathological examination. Controls group were selected as pregnant women of 1st & 2nd trimester. With the ethical approval from the institutional review board (IRB), patients were selected after taking their written consent. A structured questionnaire and a check list were designed with considering all the variables of interest.Results: Out of 50 cases 48% belongs to the age group below 20 years, 17% belongs to the age group above 34years. 88% of the control groups are belongs to the age group 20-34 years. Out of 50 cases 4% had history of prior molar pregnancy, none of the control groups had prior history of mole. 46% of molar cases belongs to the blood group A, 82% in case group and 86% of control group were hormonal contraceptive users. Among the socio-demographic risk factors occupation, education, socioeconomic condition, nutritional status of the case and control group were included.Conclusion: Molar pregnancy largely remains as etiologic dilemma. No pregnancy is immune to develop as hydatidiform mole. As the risk factors for the disease are unclear, an attempt has been made to identify some risk factors of molar pregnancy to compare them with normal pregnancy to find out any modifiable factors.JOPSOM 2020; 39(2): 34-39